A double-layer coated modified ZTA ceramic particle reinforced high manganese steel matrix composite material and its preparation method

By using a double-layer coating modification method involving CuTi alloy powder and Ni powder with high-carbon manganese iron powder, the problem of poor wettability in ZTA/HMS composite materials was solved, achieving chemical metallurgical bonding between ZTA particles and the high-manganese steel matrix, thereby improving the wear resistance and service life of the material.

CN123039341APending Publication Date: 2026-11-06JINAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611312833.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-11-06

Smart Images

  • Figure CN123039341A_ABST
    Figure CN123039341A_ABST
Patent Text Reader

Abstract

This invention provides a double-layer coated modified ZTA ceramic particle reinforced high-manganese steel matrix composite material and its preparation method, belonging to the technical field of powder metallurgy and wear-resistant metal matrix composite material preparation. Through a two-stage coating process, ZTA ceramic particles are sequentially coated with CuTi-high-carbon manganese iron powder and Ni-high-carbon manganese iron powder to prepare a double-layer coated modified ZTA ceramic preform. The high-carbon manganese iron powder can readily interfuse with the high-manganese steel melt, forming a transition channel; the CuTi-high-carbon manganese iron powder can activate the surface of the ZTA ceramic particles, constructing a reaction layer; and the Ni-high-carbon manganese iron powder can reduce the wetting angle and improve melt penetration. Furthermore, when using a casting-infiltration molding process to prepare the high-manganese steel matrix composite material, the CuTi powder, Ni powder, and high-carbon manganese iron powder exhibit a synergistic effect, promoting interfacial chemical reactions between the components and achieving a chemical metallurgical bond between the ceramic preform and the high-manganese steel matrix, thereby improving the wear resistance and service life of the high-manganese steel matrix composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of powder metallurgy and wear-resistant metal matrix composite material preparation technology. More specifically, this invention relates to a double-layer coated modified ZTA ceramic particle reinforced high manganese steel matrix composite material and its preparation method. Background Technology

[0002] Wear and failure of heavy machinery components is a thorny problem in industrial production, leading not only to resource waste but also to increased production costs. Impact wear is particularly common in many industrial settings such as coal mining, tunneling, and mining, affecting components like crusher liners, hammers, and excavator shovel teeth. High manganese steel (HMS), a traditional wear-resistant material, is widely used in applications requiring impact wear due to its excellent work hardening ability. However, conventional HMS has relatively low yield strength under low stress and limited hardening capacity, making it difficult to meet the requirements of complex operating conditions.

[0003] ZrO2-toughened Al2O3 (ZTA) ceramic particles, due to their combination of high hardness and high fracture toughness, are often used as reinforcing phases in steel-based wear-resistant composites. Therefore, ZTA-reinforced high-manganese steel matrix composites have become a highly promising advanced material for impact and wear resistance. However, current research on ZTA / HMS composites is still relatively limited. This is mainly due to the poor wettability between ZTA particles and the high-manganese steel matrix, making it difficult to form a metallurgical bonding interface between ZTA and HMS. Therefore, developing a metallurgically bonded ZTA / HMS matrix composite and its preparation method has significant research and application value. Summary of the Invention

[0004] This invention aims to address the shortcomings of existing technologies by providing a method for preparing a double-layer coated modified ZTA ceramic preform.

[0005] Another object of the present invention is to provide a double-layer coated modified ZTA ceramic preform prepared by the above method.

[0006] Another object of the present invention is to provide a method for preparing a double-layer coated modified ZTA ceramic particle reinforced high manganese steel matrix composite material.

[0007] Another object of the present invention is to provide a double-layer coated modified ZTA ceramic particle reinforced high manganese steel matrix composite material prepared by the above method.

[0008] Another object of the present invention is to provide the application of the high-manganese steel matrix composite material reinforced by the above-mentioned double-layer coated modified ZTA ceramic particles.

[0009] To achieve the above objectives, the present invention adopts the following technical solution: This invention protects a method for preparing a double-layer coated modified ZTA ceramic preform, comprising the following steps: A method for preparing a double-layer coated modified ZTA ceramic preform, characterized by the following steps: S1. CuTi-high carbon ferromanganese powder is prepared by mixing CuTi alloy powder and high carbon ferromanganese powder through ball milling; S2. Ni-high carbon ferromanganese powder is prepared by mixing Ni powder and high carbon ferromanganese powder through ball milling; S3. Mix liquid binder, CuTi-high carbon manganese iron powder, and ZTA ceramic particles, and obtain modified ZTA ceramic particles by vacuum sintering; S4. The modified ZTA ceramic particles, Ni-high carbon manganese iron powder, and liquid binder are mixed and then placed in a graphite mold and sintered under vacuum to obtain a ceramic preform; In step S1, the Ti content in the CuTi alloy powder is 10~50 wt.%.

[0010] The inventors discovered that while modifying ZTA ceramic particles with CuTi alloy powder alone could activate the ceramic and form an interfacial reaction layer, the melt exhibited poor fluidity and rapid cooling when poured into high-manganese steel, making it difficult to fully wet the preform. Through extensive experimentation, the inventors opted to premix CuTi alloy powder and Ni powder with high-carbon ferromanganese powder, respectively. The high-carbon ferromanganese powder exhibited good intermelling with the high-manganese steel melt, forming a transition channel; the CuTi-high-carbon ferromanganese powder activated the surface of the ZTA ceramic particles, constructing a reaction layer; and the Ni-high-carbon ferromanganese powder reduced the wetting angle and improved melt penetration. When the ceramic preform prepared using this method was combined with the high-manganese steel melt, the CuTi powder, Ni powder, and high-carbon ferromanganese powder exhibited a synergistic effect, promoting interfacial chemical reactions between the components. Ultimately, this resulted in the formation of a multi-layered, continuous, dense reaction layer between the ZTA particles and the high-manganese steel matrix, achieving a chemical-metallurgical bond between the ceramic preform and the high-manganese steel matrix.

[0011] Preferably, the Ti content in the CuTi alloy powder is 10~20 wt.%.

[0012] Ti is a key element for achieving metallurgical bonding. At high temperatures, it reacts chemically with O in ZTA ceramics and also forms chemical bonds with C in high-carbon manganese iron. Therefore, it is generally believed that a higher Ti content is more conducive to interfacial reaction bonding. However, using the solution of this invention, even with CuTi powder of low Ti content, a tight chemical metallurgical bond can still be achieved on the ZTA surface.

[0013] Preferably, the particle size of ZTA ceramic particles is 8-12 mesh.

[0014] Preferably, the high-carbon ferromanganese powder is an iron-manganese alloy with a carbon content of 2-8%.

[0015] More preferably, the high-carbon ferromanganese powder is an iron-manganese alloy with a carbon content of 4-8%. Within the preferred range, the high-carbon ferromanganese has a higher melting point, which is closer to the casting temperature of high-manganese steel melt.

[0016] Preferably, in step S1, the CuTi alloy powder, high-carbon manganese iron powder, and Ni powder all have a particle size of 300-400 mesh.

[0017] Preferably, in step S1, the mass ratio of CuTi alloy powder to high-carbon ferromanganese powder is (3~8):(2~7).

[0018] Preferably, in step S2, the mass ratio of Ni powder to high-carbon manganese iron powder is (2~5):(3~7).

[0019] Preferably, in step S3, the mass ratio of ZTA ceramic particles to CuTi-high carbon manganese iron powder is 100:(30~40).

[0020] Preferably, in step S4, the mass ratio of modified ZTA ceramic particles to Ni-high carbon manganese iron powder is 100:(10~20).

[0021] Preferably, the liquid adhesive is at least one of a PVA solution or a PVB solution; the PVA solution is an aqueous solution of polyvinyl alcohol, and the PVB solution is an aqueous solution of polyvinyl butyral.

[0022] More preferably, the liquid adhesive is a PVB solution.

[0023] Preferably, the concentration of the liquid binder is 10~15 wt.%.

[0024] Preferably, in step S3, the mass ratio of the mixed powder of CuTi-high carbon manganese iron powder and ZTA ceramic particles to the liquid binder is (20~40):(3~7).

[0025] Preferably, in step S4, the mass ratio of the mixed powder of Ni-high carbon manganese iron powder and ZTA ceramic particles to the liquid binder is (20~40):(3~7).

[0026] Preferably, the ball milling mixing process conditions are as follows: ball milling time is 600~900 min, grinding ball diameter is 10~15 mm, ball-to-material ratio is (3~5):1, and ball milling speed is 200~300 r / min; and the ball milling mixing is carried out under inert gas protection, wherein the inert gas is one of argon, helium and nitrogen.

[0027] More preferably, the inert gas is argon.

[0028] Preferably, in step S3, the vacuum sintering temperature is 1050~1200 ℃, the holding time is 60~90 min, and the vacuum degree is 10. -3 Pa; Preferably, in step S4, the vacuum sintering temperature is 1300~1450 ℃, the vacuum sintering holding time is 120~180 min, and the vacuum degree of vacuum sintering is 10. -3 Pa.

[0029] This invention protects a double-layer coated modified ZTA ceramic preform prepared by the above method.

[0030] This invention protects a method for preparing a double-layer coated modified ZTA ceramic particle reinforced high manganese steel matrix composite material, comprising the following steps: fixing the above-mentioned ZTA ceramic preform in a mold cavity, pouring high manganese steel melt, and cooling to obtain the ZTA ceramic particle reinforced high manganese steel matrix composite material.

[0031] Preferably, the high-manganese steel has the following composition: C (1.05~1.35%), Si (0.30~0.90%), Mn (11~14%), P (≤0.06%), S (≤0.04%), with the balance being Fe, all of which are mass percentages.

[0032] Preferably, the furnace tapping temperature of the high-manganese steel melt is 1530~1580 ℃, and the casting temperature is 1490~1510 ℃.

[0033] This invention protects a double-layer coated modified ZTA ceramic particle reinforced high-manganese steel matrix composite material prepared by the above method.

[0034] This invention also protects the application of the above-mentioned double-layer coated modified ZTA ceramic particle reinforced high manganese steel matrix composite material in the fields of metallurgy, mining, construction, machinery or power.

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows: CuTi powder and high-carbon ferromanganese powder are used to in-situ activate and modify ZTA particles at the interface, reducing the wetting angle between ZTA particles and the metal. A second coating of ZTA particles with Ni powder and high-carbon ferromanganese powder further improves the wettability and penetration of ZTA particles by molten high-manganese steel, mitigating the defect caused by the rapid cooling rate of the molten high-manganese steel preventing sufficient penetration of the ZTA ceramic preform. This results in a strong chemical-metallurgical bond between the ZTA ceramic preform and the high-manganese steel matrix, significantly improving the abrasion resistance and service life of the high-manganese steel-based composite material. Attached Figure Description

[0036] Figure 1 This is a SEM image of the composite material in Example 1.

[0037] Figure 2 This is an EDS line scan of the interface in Example 1.

[0038] Figure 3 This is a process flow diagram for an example.

[0039] Figure 4 This is a schematic diagram of the interface structure of composite materials. Detailed Implementation

[0040] To more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. Various changes can be made within the scope of the claims of the present invention.

[0041] Unless otherwise specified, all reagents and materials used in the following examples are commercially available.

[0042] The process flow of the embodiment is as follows Figure 3 As shown.

[0043] Example 1 S1. Weigh commercially available CuTi alloy powder (Ti content is 20% by mass) and high carbon manganese iron powder at a mass ratio of 8:7, and ball mill them at a speed of 300 r / min for 900 min. The diameter of the grinding balls is 15 mm, the ball-to-material ratio is 5:1, and the ball milling is carried out under argon protection.

[0044] S2. Weigh Ni powder and high-carbon manganese iron powder at a mass ratio of 5:7, and ball mill them at a speed of 300 r / min for 900 min. The diameter of the grinding balls is 15 mm, the ball-to-material ratio is 5:1, and the ball milling is carried out under argon protection.

[0045] S3. Weigh out 12-mesh ZTA ceramic particles, CuTi-high carbon manganese iron powder, and 15 wt.% PVB aqueous solution at a mass ratio of 100:40:7. First, mix the ZTA ceramic particles with the PVB aqueous solution, then add the CuTi-high carbon manganese iron powder and stir evenly. After the mixed powder fully coats the ZTA particles, place it in a vacuum sintering furnace and sinter at 1200 ℃ for 90 min, maintaining a vacuum degree of 10. - 3 Pa.

[0046] S4. Weigh the modified ZTA ceramic particles, Ni-high carbon manganese iron powder, and 15 wt.% PVB aqueous solution at a mass ratio of 100:20:3. First, mix the modified ZTA ceramic particles with the PVB aqueous solution, then add the Ni-high carbon manganese iron powder and stir evenly. After the mixed powder fully coats the ZTA particles, place it in a graphite mold and sinter it in a vacuum sintering furnace at 1450 ℃ for 180 min, maintaining a vacuum degree of 10. -3 Pa. Demolding yields the ceramic preform.

[0047] S5. ZTA ceramic particle-reinforced high-manganese steel matrix composite material was prepared using a casting infiltration method. The ZTA ceramic preform was fixed inside the mold cavity using coarse iron wire, and molten high-manganese steel was poured in. The furnace exit temperature of the molten high-manganese steel was controlled at 1530~1580 ℃, and the casting temperature was controlled at 1490~1510 ℃. Slag removal and deoxidation treatments were performed before casting.

[0048] Figure 1 , Figure 2 These are scanning electron microscope (SEM) images and EDS line scan images of the double-layer coated modified ZTA ceramic particles reinforced high-manganese steel matrix. Figure 4 A schematic diagram of the prepared modified ZTA ceramic particle-reinforced high-manganese steel matrix composite material is shown. As can be seen from the figure, a continuous and dense in-situ reaction layer with elemental gradient transition was successfully constructed between the ZTA ceramic particles and the high-manganese steel matrix through a double-layer coating of CuTi-high-carbon manganese iron powder and Ni-high-carbon manganese iron powder, achieving true chemical metallurgical bonding.

[0049] Example 2 S1. Weigh commercially available CuTi alloy powder (Ti content is 20% by mass) and high carbon manganese iron powder at a mass ratio of 6:5, and ball mill them at a speed of 250 r / min for 750 min. The diameter of the grinding balls is 13 mm and the ball-to-material ratio is 4:1. The ball milling is carried out under argon protection.

[0050] S2. Weigh Ni powder and high-carbon manganese iron powder at a mass ratio of 4:3, and ball mill them at a speed of 250 r / min for 750 min. The diameter of the grinding balls is 13 mm, the ball-to-material ratio is 4:1, and the ball milling is carried out under argon protection.

[0051] S3. Weigh out 12-mesh ZTA particles, CuTi-high carbon manganese iron powder, and 13 wt.% PVB aqueous solution at a mass ratio of 100:35:6. First, mix the ZTA ceramic particles with the PVB aqueous solution, then add the CuTi-high carbon manganese iron powder and stir evenly. After the mixed powder fully coats the ZTA ceramic particles, place it in a vacuum sintering furnace and sinter at 1100 ℃ for 75 min, maintaining a vacuum degree of 10. -3 Pa.

[0052] S4. Weigh the modified ZTA particles, Ni-high carbon manganese iron powder, and 13 wt.% PVB aqueous solution at a mass ratio of 100:15:1.5. First, mix the modified ZTA ceramic particles with the PVB aqueous solution, then add the Ni-high carbon manganese iron powder and stir evenly. After the mixed powder fully coats the ZTA ceramic particles, place it in a graphite mold and sinter it in a vacuum sintering furnace at 1350 ℃ for 160 min, maintaining a vacuum degree of 10. -3 Pa. Demolding yields the ceramic preform.

[0053] S5. ZTA ceramic particle-reinforced high-manganese steel matrix composite material was prepared using a casting infiltration method. The ZTA ceramic preform was fixed inside the mold cavity using coarse iron wire, and molten high-manganese steel was poured in. The furnace exit temperature of the molten high-manganese steel was controlled at 1530~1580 ℃, and the casting temperature was controlled at 1490~1510 ℃. Slag removal and deoxidation treatments were performed before casting.

[0054] Example 3 S1. Weigh commercially available CuTi alloy powder (Ti content is 20% by mass) and high carbon manganese iron powder at a mass ratio of 3:2, and ball mill them at a speed of 200 r / min for 600 min. The diameter of the grinding balls is 10 mm and the ball-to-material ratio is 3:1. The ball milling is carried out under argon protection.

[0055] S2. Weigh Ni powder and high-carbon manganese iron powder at a mass ratio of 2:3, and ball mill them at a speed of 200 r / min for 600 min. The diameter of the grinding balls is 10 mm, the ball-to-material ratio is 3:1, and the ball milling is carried out under argon protection.

[0056] S3. Weigh out 12-mesh ZTA particles, CuTi-high carbon manganese iron powder, and 10 wt.% PVB aqueous solution at a mass ratio of 100:30:3. First, mix the ZTA ceramic particles with the PVB aqueous solution, then add the CuTi-high carbon manganese iron powder and stir evenly. After the mixed powder fully coats the ZTA ceramic particles, place it in a vacuum sintering furnace and sinter at 1050 ℃ for 60 min, maintaining a vacuum degree of 10. -3 Pa.

[0057] S4. Weigh the modified ZTA particles, Ni-high carbon manganese iron powder, and 13 wt.% PVB aqueous solution at a mass ratio of 100:10:2. First, mix the modified ZTA ceramic particles with the PVB aqueous solution, then add the Ni-high carbon manganese iron powder and stir evenly. After the mixed powder fully coats the ZTA ceramic particles, place them in a graphite mold and sinter in a vacuum sintering furnace at 1300 ℃ for 120 min, maintaining a vacuum degree of 10. -3 Pa. Demolding yields the ceramic preform.

[0058] S5. ZTA ceramic particle-reinforced high-manganese steel matrix composite material was prepared using a casting infiltration method. The ZTA ceramic preform was fixed inside the mold cavity using coarse iron wire, and molten high-manganese steel was poured in. The furnace exit temperature of the molten high-manganese steel was controlled at 1530~1580 ℃, and the casting temperature was controlled at 1490~1510 ℃. Slag removal and deoxidation treatments were performed before casting.

[0059] Example 4 The implementation method is the same as in Example 1, except that the CuTi alloy powder is a mixture of Cu powder and Ti powder obtained by ball milling, wherein the Ti content is 20 wt.%. The ball milling process is as follows: the diameter of the grinding ball is 8~15 mm, the weight ratio of the grinding ball to the mixed powder is 15:1, the rotation speed is 400~450 r / min, and the ball milling time is 50 h.

[0060] Comparative Example 1 S1. Ultrasonically clean 12-mesh ZTA particles with alcohol, then dry them for later use. Weigh an appropriate amount of ZTA particles and water glass binder, with the water glass binder accounting for 10% of the total mass. Thoroughly mix the ZTA particles and water glass binder, then load the ZTA particles into a graphite mold to prepare a preform, and apply pressure to compact the ZTA particles. Place the mold in a drying oven at 80 ℃ for 5 h, and after drying, demold to obtain the ZTA ceramic preform.

[0061] S2. ZTA particle-reinforced high-manganese steel matrix composites were prepared using a casting infiltration method. ZTA ceramic preforms were fixed inside the mold cavity using coarse iron wire, and molten high-manganese steel was poured in. The furnace exit temperature of the molten high-manganese steel was controlled at 1530~1580 ℃, and the casting temperature was controlled at 1490~1510 ℃. Slag removal and deoxidation treatments were performed before casting.

[0062] In Comparative Example 1, water glass was used as a transition layer. There was no interfacial reaction between ZTA and high manganese steel liquid. ZTA and high manganese steel were mechanically bonded, but the bonding force was weak. Moreover, obvious physical gaps could be seen at the interface under a high-magnification electron microscope, indicating that the interface connection was incomplete.

[0063] Comparative Example 2 S1. Weigh commercially available CuTi alloy powder (Ti content is 20% by mass) and high carbon manganese iron powder at a mass ratio of 8:7, and ball mill them at a speed of 300 r / min for 900 min. The diameter of the grinding balls is 15 mm, the ball-to-material ratio is 5:1, and the ball milling is carried out under argon protection.

[0064] S2. Weigh out 12-mesh ZTA particles, CuTi-high carbon manganese iron powder, and 10 wt.% PVB aqueous solution at a mass ratio of 100:30:3. First, mix the ZTA ceramic particles with the PVB aqueous solution, then add the CuTi-high carbon manganese iron powder and stir until homogeneous. After fully coating the ZTA particles with the mixed powder, place the mixture into a graphite mold and sinter it in a vacuum sintering furnace at 1050 ℃ for 60 min, maintaining a vacuum degree of 10. -3 Pa. Demolding yields the ceramic preform.

[0065] S3. ZTA ceramic particle-reinforced high-manganese steel matrix composite material was prepared using a casting infiltration method. The ZTA ceramic preform was fixed inside the mold cavity using coarse iron wire, and molten high-manganese steel was poured in. The furnace exit temperature of the molten high-manganese steel was controlled at 1530~1580 ℃, and the casting temperature was controlled at 1490~1510 ℃. Slag removal and deoxidation treatments were performed before casting.

[0066] In Comparative Example 2, ZTA was modified using only CuTi-high carbon manganese iron powder, and the composite material was obtained by casting. Compared with Example 1, due to the lack of Ni-high carbon manganese iron powder, the high manganese steel liquid could not penetrate the defects of the ZTA preform well, and could not achieve a significant improvement effect.

[0067] The high-manganese steel-based composite materials prepared in the examples and comparative examples were subjected to impact abrasive wear tests (MLD-10 impact abrasive wear testing machine). The test parameters were: impact energy 3 J / cm. 2 The abrasive used was #6 quartz sand, the sample rotation speed was 155 r / min, the sample material was 45# steel, and the time was 60 min (15 min × 5 times). The impact abrasive wear rates of the composite materials prepared in Examples 1-4 and Comparative Examples 1-2 are shown in the table below.

[0068] Table 1

[0069] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a double-layer coated modified ZTA ceramic preform, characterized in that, Includes the following steps: S1. CuTi-high carbon ferromanganese powder is prepared by mixing CuTi alloy powder and high carbon ferromanganese powder through ball milling; S2. Ni-high carbon ferromanganese powder is prepared by mixing Ni powder and high carbon ferromanganese powder through ball milling; S3. Mix liquid binder, CuTi-high carbon manganese iron powder, and ZTA ceramic particles, and obtain modified ZTA ceramic particles by vacuum sintering; S4. The modified ZTA ceramic particles, Ni-high carbon manganese iron powder, and liquid binder are mixed and then placed in a graphite mold and sintered under vacuum to obtain a ceramic preform; In step S1, the Ti content in the CuTi alloy powder is 10~50 wt.%.

2. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of Ni powder to high-carbon iron manganese powder is (2~5):(3~7).

3. The method according to claim 1, characterized in that, In step S3, the mass ratio of ZTA ceramic particles to CuTi-high carbon manganese iron powder is 100:(30~40).

4. The preparation method according to claim 1, characterized in that, In step S4, the mass ratio of modified ZTA ceramic particles to Ni-high carbon manganese iron powder is 100:(10~20).

5. The preparation method according to claim 1, characterized in that, In step S3, the vacuum sintering temperature is 1050~1200 ℃, and the vacuum sintering holding time is 60~90 min.

6. The preparation method according to claim 1, characterized in that, In step S4, the vacuum sintering temperature is 1300~1450 ℃, and the vacuum sintering holding time is 120~180 min.

7. A double-layer coated modified ZTA ceramic preform, characterized in that, Prepared by the method described in any one of claims 1 to 6.

8. A method for preparing a double-layer coated modified ZTA ceramic particle reinforced high-manganese steel matrix composite material, characterized in that, The ZTA ceramic preform described in claim 1 is fixed in a mold cavity, high manganese steel melt is poured in, and then cooled to obtain a ZTA ceramic particle reinforced high manganese steel matrix composite material.

9. A double-layer coated modified ZTA ceramic particle reinforced high-manganese steel matrix composite material, characterized in that, It is prepared by the method described in claim 9.

10. The application of the double-layer coated modified ZTA ceramic particle reinforced high manganese steel matrix composite material as described in claim 10 in the fields of metallurgy, mining, construction, machinery or power.